Growth, Phytochemicals, and Antioxidant Activity of Kale Grown under Different Nutrient-Solution Depths in Hydroponic - Jiehui Tan; Haozhao Jiang; Yamin Li; Rui He; Kaizhe Liu; Yongkang Chen; Xinyang He; Xiaojuan Liu; Houcheng Liu (Horticulturae, 2023)
To explore the effect of different nutrient-solution depths on the growth and phytochemicals accumulation of kale, three different nutrient-solution depth treatments (De-1: 1 cm, De-2: 2 cm, and De-3: 3 cm) were applied in the plant factory with artificial lighting. The maximum levels of plant height, stem diameter, total leaf area, total root length, and root surface area as well as fresh and dry weight of the shoot and root were all noted in De-2 at 24 days after treatment. Low nutrient-solution depth treatments (De-1 and De-2) were beneficial for total chlorophyll accumulation and nutrient ions uptake (N, P, K, Ca, S, and Zn). However, there were no obvious differences in DPPH and FRAP as well as contents of total polyphenols and flavonoids. In high nutrient-solution depth treatment (De-3), the contents of carotenoid, soluble sugars, and vitamin C were higher than those in De-1 and De-2. The contents of total glucosinolates (GLs), aliphatic GLs, and indole GLs significantly increased in kale under De-3. Higher contents of reactive oxygen species (ROS), hydrogen peroxide (H2O2), oxalate oxidase (OXO), and proline were observed in kale roots under De-2 and De-3. Overall, 2 cm of nutrient-solution depth could be used to promote kale growth, and 3 cm may represent a potential approach for improving kale quality in a plant factory.